Determination of the contributionof the exciton-phonon interaction inthe processes of electronicexcitations self-trapping in alkalihalide crystals - Мясниковa, Л.Н.; Сaгимбaевa, Ш.Ж.; Шункеев, К.Ш. (Recent Contributions to Physics, 2016)
The paper is about the question of the exciton-phonon interaction in alkali halide crystals at low temperature deformation. The frequency of active modes of self-trapped excitons was calculated and the parameter of the Huang-Rhys was estimated with harmonic approximation, which has an optical bandwidth half-width dependence on temperature both before and after deformation. The increase in the value of the oscillation frequency after deformation indicates a change in the form of the adiabatic potential curve of the excited state of self-trapped excitons in alkali halide crystals.